2007
DOI: 10.1016/j.bbrc.2006.12.236
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of a hepatic phenotype after heterotropic transplantation of heart, kidney, brain, and skin tissues into liver in F344 rats

Abstract: While organ-specific stem cells with roles in tissue injury repair have been documented, their pathogenic significance in diseases and the factors potentially responsible for their activation remain largely unclear. In the present study, heart, kidney, brain, and skin samples from F344 transgenic rats carrying the GFP gene were transplanted into normal F344 rat liver one day after an intraperitoneal injection (i.p.) of carbon tetrachloride (CCl(4)) to test their differentiation capacity. The transplantation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…22 These findings indicate that MSCs possess the potential to differentiate into hepatic lineage, but the mechanism remains unclear. MSC differentiation is known to be mediated by a local niche environment in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…22 These findings indicate that MSCs possess the potential to differentiate into hepatic lineage, but the mechanism remains unclear. MSC differentiation is known to be mediated by a local niche environment in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, bone marrow cells developed into hepatocytes when transplanted in vivo [15]. These findings indicate that bone marrow cells possess the potential to differentiate into hepatic lineage, but the mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 96%
“…They demonstrated continuous GFP expression, driven by the liver-specific albumin enhancer/promoter, in transplanted hepatocytes up to four months after transplantation. Other studies showed repopulation of injured liver tissue by transplanted syngeneic stem/progenitor cells expressing GFP [8], [9]. Therefore, we expected to see long-term survival of GFP-positive hepatocytes after transplantation into a wild-type Lewis rat liver.…”
Section: Introductionmentioning
confidence: 92%